Identification of building reliability with a forensic audit of the Non Destructive Test method - Wahyudi Efendi, ST., MT., ASEAN Eng., ACPE., Ir. Aco (Jurnal Informasi, Sains dan Teknologi, 2022)
Forensic engineering is the analysis of objects and buildings that fail to perform or do not work as intended, resulting in personal injury or property damage. Experimental analysis was carried out in this study using non-destructive tools on the structural elements of the building being evaluated and providing information in the form of identification of damage from the results of forensic audits at the reviewed OJK Samarinda building. According to the findings of study utilizing the damage identification technique (forensic audit) employing the NDT instrument in OJK office buildings, the homogeneity of the concrete in the structural elements of the building's beams and columns is good to very good. This is evident from the velocity values found in the concrete pieces. It varies between > 3000 m/s and When the compressive strength of concrete is greater than fc' 28 MPa, the amount of reinforcement in the beam and column elements examined exceeds the reinforcement requirement in the beam and column structural elements of the building, in terms of cracks that occur in the beam and column structural elements. The damage to the architectural components was discovered on the building's walls.